Methods of the audiovisual activating of organs and systems studying in the process of educating (Experimental biology, 2015)
The methods of the audiovisual activating of organs and systems of studying are examined at the level of wavebiological processes. The method of activating of centers of perceptible perception of sound and color allows tosynchronize the processes of development of sense-organs and speech, accelerating development of student the same.
Keywords: centers of perceptible perception; rhythms of brain; physical and spiritual health of man; harmonization